Ergonomics risk assessment among manual handling workers - Wichai, Janjiraporn; Chaiklieng, Sunisa (Asia-Pacific Journal of Science and Technology, 2017)
The aim of this survey research was to assess the ergonomic risks of workers whose jobs involved manual lifting and handling of industrial materials. The subjects were workers in two factories, and data were collected with an interview questionnaire and by observation and the use of the Rapid Entire body assessment (REBA) and the NIOSH lifting equation. Most workers were male, 60.0% were aged 20 to 29 years , and 58.6% had sixmonths to 20 years work experience. The average weight oflifted materials was 15.2 kg (SD = 4.8), and most workers (77.1%) lifted materials more than 500 times per day. The REBA results indicated that 48.6% were exposed to a very high ergonomic risk (level 4: should be improved or corrected immediately), and that for 41.4% the risk was high (level 3: should be examined and resolved soon). The filing and repair ofgas containers were tasks involving high ergonomic risk. The NIOSH lifting equation confimed the ergonomics risk in terms of lifting indices (LI) >1 and recommended weight limits (RWL) exceeding 100% for the same process. The results of two differentmethods of ergonomic risk assessment were consistent with eachother. Employees shouldbe given training in safeways of manual handling/lifting to minimize the associated ergonomic risk and prevent backpain or musculoskeletal injuries.